2012
DOI: 10.1143/jjap.51.020204
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the Light Output Power of GaN-Based Light-Emitting Diodes with Nanotextured Indium Tin Oxide Layer Using Self-Assembled Cesium Chloride Nanospheres

Abstract: In this study, enhanced light output power in GaN-based light-emitting diodes (LEDs) with a nanotextured indium tin oxide (ITO) transparent conductive layer was observed. Wafer-scale self-assembled cesium chloride nanospheres were formed on the ITO transparent conductive layer and served as the mask in a dry etching process. After the inductively coupled plasma (ICP) etching process, nanoscale islands were fabricated on the ITO layer. Compared with LEDs with a planar ITO layer, the light output power of LEDs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, the total internal reflection occurring at the interface between the GaN ( n = 2.5), the smooth ITO ( n = 2.08), and the ambient air ( n = 1) limits the light extraction efficiency. It was previously demonstrated that the light extraction efficiency of LEDs can be improved by intentionally roughening LED surface . A similar concept has also been applied to LED chip sidewalls, and more photons might escape from LEDs with textured sidewalls as compared to LEDs with flat sidewalls .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the total internal reflection occurring at the interface between the GaN ( n = 2.5), the smooth ITO ( n = 2.08), and the ambient air ( n = 1) limits the light extraction efficiency. It was previously demonstrated that the light extraction efficiency of LEDs can be improved by intentionally roughening LED surface . A similar concept has also been applied to LED chip sidewalls, and more photons might escape from LEDs with textured sidewalls as compared to LEDs with flat sidewalls .…”
Section: Introductionmentioning
confidence: 99%